Range of host plants, spatial distribution, and insect predator of Phenacoccus manihoti (Hemiptera: Pseudococcidae) as an emerging pest of cassava plants in Bali, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Supartha IW, Widaningsih D, Susila IW, Yudha IKW, Utama IWEK, Wiradana PA. 2022. Range of host plants, spatial distribution, and insect predator of Phenacoccus manihoti (Hemiptera: Pseudococcidae) as an emerging pest of cassava plants in Bali. Biodiversitas 23: 3022-3030. The cassava mealybug Phenacoccus manihoti (Hemiptera: Pseudococcidae) is a very destructive pest in cassava farming in Indonesia. The insect has already made its way into Indonesia, where it has attacked cassava plants with indications of a bunchy top, which may cause plant death. The objectives of this study were to 1) discover and identify an invasive pest of cassava mealybug pest, P. manihoti, that attacks cassava plants in Bali; 2) map the distribution and abundance of these pest species populations on cassava plants in Bali; 3) describe the structure of the pest population in cassava plantations in Bali; 4) identify the dominant factors that influence the population structure of P. manihoti in Bali, and 5) evaluate the predator fauna in regulating the population. The findings revealed that the mealybug species that attacked cassava in Bali was P. manihoti, an exotic species that had never been published earlier. With a high population abundance, the pest has spread far and effectively overall in regencies/cities in Bali Province. In all regency/city regions, the population structure of P. manihoti was dominated by age groups of instar-1 and two nymphs, with the exception of the Buleleng Regency, which was dominated by age groups of nymphs instar 3 and 4. The nature of polyphagy and cosmopolite features that are readily adaptable to the environment and host plant variables, farming pattern, temperature and rainfall factors were the key factors impacting the population structure of P. manihoti in the field. Cryptolaemus montrouzieri, Chrysoperla carnea, and Scymnus sp. were discovered to have a role in managing P. manihoti populations in the field. The predator fauna community is structurally diverse, abundant, and has a low dominance. Cryptolaemus montrouzieri was the most dominant of the three producer species in the field. These results indicate that there is a positive potential shown by predatory mealybugs in the field and can be used as an initial model by related parties in formulating policies related to controlling insect pests of cassava plants.
Keywords: Invasive pests; Phenacoccus manihoti; Predatory fauna; Cassava crop; Biocontrol